No evidence of Borrelia in cutaneous infiltrates of B‐cell lymphomas with a highly sensitive, semi‐nested real‐time polymerase chain reaction targeting the 5S‐23S intergenic spacer region. (10th March 2022) - Papadopoulou, K.; Falk, T.M.; Metze, D.; Böer‐Auer, A.
Abstract: Background: The role of Borrelia in the development of skin lymphomas has been under discussion for decades. A similar association has been shown for Helicobacter pylori and gastric lymphomas (MALT type). Nevertheless, few molecular studies investigated Borrelia in skin lymphomas and the results are controversial. Methods: We analysed 46 formalin‐fixed, paraffin‐embedded skin specimens of clincopathologically confirmed B‐cell lymphomas (15 marginal zone lymphomas; 20 follicular lymphomas; three diffuse large B‐cell lymphomas; eight secondary cutaneous infiltrates) taken from 36 patients from Northern Germany, an endemic area for Borrelia . Fifteen pseudolymphomatous lesions of cutaneous Borreliosis served as the control. Both groups were examined with a real‐time (rt) PCR and a semi‐nested PCR targeting the 5S‐23S intergenic spacer region (IGS). A multiplex PCR was used to investigate B‐cell clonality in all lymphomatous infiltrates (Biomed Primers). Results: With both assays no Borrelia burgdorferi ‐specific DNA was identified in any of the B‐cell lymphomas, while all 15 Borreliosis specimens gave a positive PCR result in the semi‐nested PCR protocol, 12 were also positive in the rt PCR ( P < 0.01). All B‐cell lymphomas showed monoclonal IgH‐Rearrangement. Analysis of cutaneous B‐cell lymphomas from available studies including ours ( n = 334) reveals an odds ratio <1. Conclusion: While some previous studies suggested an association between B. burgdorferi and the development of cutaneous B‐cell lymphomas in endemic areas, we were unable to confirm this in our patients, despite a highly sensitive Borrelia PCR assay. Our results including meta‐analysis of previous studies question the need for antibiotic therapy in patients with cutaneous B‐cell lymphomas.